Hospital liquid waste treatment: a review - Arifin, Achmad Syifa Ul Qulub Al; Nabil, Ahmad Jazuly (Universitas Nahdlatul Ulama Surabaya, 2023)
Hospital activities affect the condition of the waste produced, especially liquid waste, which can cause environmental pollution and cause health problems. Hospital waste comes from waste from the nutrition kitchen and canteen, laundry, laboratory, x-ray, and radiotherapy. Therefore, it is necessary to manage hospital wastewater properly and correctly, so that the hospital environment becomes healthy, comfortable, and sustainable. This study on the processing of hospital liquid waste uses a literature review method. The population is 3 (three) journals. The keywords used are hospitals, wastewater, IPAL. Analysis using PICOS. Results: This study conducted data analysis on several previous studies aimed at obtaining the results of the study so that they were able to find facts that could be used as evidence. Based on the table above, it can be seen that of the 3 (three) journals, 1 (two) of them did not meet the quality standards for hospital liquid waste and 2 (two) of them met the quality standards for hospital liquid waste. Management of hospital liquid waste in Indonesia. Wastewater from the nutrition kitchen, laundry, and laboratory must undergo special treatment before going to the IPAL. In the IPAL, processing is carried out until thewastewater meets the standard for liquid waste quality and is suitable for release into the environment.